The ITGAV rs3738919 variant and susceptibility to rheumatoid arthritis in four Caucasian sample sets. - Hollis-Moffatt, J; Rowley, K; Phipps-Green, A; Merriman, M; Dalbeth, N; Gow, P; Harrison, A; Highton, J; Jones, P; Stamp, L; Harrison, P; Wordsworth, B; et al. (BioMed Central, 2009)
INTRODUCTION: Angiogenesis is an important process in the development of destructive synovial pannus in rheumatoid arthritis (RA). The ITGAV +gene encodes a cell cycle-associated antigen, integrin alphanubeta 3, which plays a role in RA angiogenesis. Previously, two independent studies identified an association between the major allele of the ITGAV single-nucleotide polymorphism (SNP) rs3738919 and RA. We therefore tested this association in an independent study using New Zealand (NZ) and Oxford (UK) RA case control samples. METHODS: We compared genotype frequencies in 740 NZ Caucasian RA patients and 553 controls genotyped for rs3738919, using a polymerase chain reaction-restriction fragment length polymorphism assay. A TaqMan genotyping SNP assay was used to type 713 Caucasian RA patients and 515 control samples from Oxford for the rs3738919 variant. Association of rs3738919 with RA was tested in these two sample sets using the chi-square goodness-of-fit test. The Mantel-Haenszel test was used to perform a meta-analysis, combining the genetic results from four independent Caucasian case control cohorts, consisting of 3,527 cases and 4,126 controls. Haplotype analysis was also performed using SNPs rs3911238, rs10174098 and rs3738919 in the Wellcome Trust Case Control Consortium, NZ and Oxford case control samples. RESULTS: We found no evidence for association between ITGAV and RA in either the NZ or Oxford sample set (odds ratio [OR] = 0.88, P(allelic) = 0.11 and OR = 1.18, P(allelic) = 0.07, respectively). Inclusion of these data in a meta-analysis (random effects) of four independent cohorts (3,527 cases and 4,126 controls) weakens support for the hypothesis that rs3738919 plays a role in the development of RA (OR(combined) = 0.92, 95% confidence interval 0.80 to 1.07; P = 0.29). No consistent haplotype associations were evident. CONCLUSIONS: Association of ITGAV SNP rs7378919 with RA was not replicated in NZ or Oxford case control sample sets. Meta-analysis of these and previously published data lends limited support for a role for the ITGAV in RA in Caucasians of European ancestry.